Computational identification of Vernonia cinerea-derived phytochemicals as potential inhibitors of nonstructural protein 1 (NSP1) in dengue virus serotype-2 - Hossain, Md. Shohel; Hasnat, Soharth; Akter, Shilpy; Mim, Maria Mulla; Tahcin, Anika; Hoque, Majedul; Sutradhar, Durjoy; Keya, Mst. Alifa Akter; Sium, Namin Rouf; Hossain, Sophia; Masuma, Runa; Rakib, Sakhawat Hossen; et al. (Frontiers in Pharmacology, 2024)
Background: Dengue virus (DENV) infection, spread by Aedes aegypti mosquitoes, is a significant public health concern in tropical and subtropical regions. Among the four distinct serotypes of DENV (DENV-1 to DENV-4), DENV-2 is associated with the highest number of fatalities worldwide. However, there is no specific treatment available for dengue patients caused by DENV-2. Objective: This study aimed to identify inhibitory phytocompounds in-silico in Vernonia cinerea (V. cinerea), a widely used traditional medicinal plant, for treating DENV-2 associated illnesses. Methods: The chemical structures of 17 compounds from V. cinerea were sourced from the Indian Medicinal Plants, Phytochemistry, and Therapeutics (IMPPAT) database. These compounds underwent geometry optimization, were screened against nonstructural protein 1 (NSP1) of DENV-2, and further validated through molecular dynamics simulations (MDS). Baicalein, an established drug against DENV-2, was used for validation in molecular screening, MDS, and MM-GBSA analyses. Results: Among these compounds, Beta-amyrin, Beta-amyrin acetate, Chrysoeriol, Isoorientin, and Luteolin showed promising potential as inhibitors of the NSP1 of DENV-2, supported by the results of thermodynamic properties, molecular orbitals, electrostatic potentials, spectral data and molecular screening. Besides, these compounds adhered to the Lipinski's "rule of 5", showing no hepatotoxicity/cytotoxicity, with mixed mutagenicity, immunotoxicity, and carcinogenicity. Furthermore, final validation through MDS confirmed their potential, demonstrating stable tendencies with significant inhibitory activities against NSP1 of DENV-2 over the control drug Baicalein. Among the screened compounds, Chrysoeriol emerged as the most promising inhibitor of NSP1 of DENV-2, followed by Luteolin and Isoorientin. Conclusion: Taken together, our results suggest that Chrysoeriol is the best inhibitor of NSP1 of DENV-2, which could be evaluated as a therapeutic agent or a lead compound to treat and manage DENV-2 infections.